Get Calves Ready for the Long Haul - Jeffrey N. Carter (EDIS)
AN174, a 2-page fact sheet by Jeffrey N. Carter, describes the advantages of following a pre-conditioning program to optimize performance, health, and ranch reputation. Includes a table with suggested nutrient concentrations in a pre-conditioning diet for beef calves. Published by the UF Department of Animal Sciences, August 2007.